An ultra-thin low-frequency broadband metasurface with near-zero suppression of aerodynamic acoustic pressure. (28th February 2023) - Li, Min; Wu, Jiuhui; Wu, Bobo; Ma, Fuyin; Liu, Chongrui; Yuan, Xiaoyang; Sun, Yangbin
Highlights: Aerodynamic acoustic pressure suppression mechanism of lotus-pods-neck HR is revealed. Realization of low-frequency aerodynamic noise control is due to larger acoustic mass. Larger absorption area ratio makes impedance nearer zero with less effect by flow. Low-frequency and broadband aerodynamic noise reduction is experimentally verified. Abstract: A near-zero suppression mechanism of aerodynamic acoustic pressure is revealed by adopting the ultra-thin low-frequency broadband lotus-pods-neck Helmholtz resonator (LPNHR) metasurface presented in this paper. The LPNHR is designed by changing the single neck of a Helmholtz resonator (HR) to a lotus-pods multi-layer-hole neck and keeping the number and equivalent diameter of the holes in the upper layer greater than that in the lower layer, and the bandwidth of LPNHR could be much widened than that of HR since the reduced acoustic mass. During the incident fluid flow, compared with HR, greater pressure difference formed at the interface of each hole of LPNHR generates stronger multi-vortexes inside its neck. Larger multi-vortex areas with greater absorption area ratio significantly increase the average flow velocity at the neck interface of LPNHR, resulting in decreased impedance. Moreover, the stronger multi-vortexes weaken the influence of the main-flow on the fluid flow inside the neck, that is, the flow from the external flow field into the LPNHR neck is enhanced under the action of the strong vortexes. The impedance decreases further and the effective length of the neck and acoustic mass increase, the shift of the flow-influenced sound attenuation to higher frequencies is suppressed and turned to lower frequencies. When the impedance approaches zero, the incident and scattered acoustic pressure match in phase and the acoustic pressure fluctuation at the wall will be fundamentally suppressed. Which is the physical mechanism of LPNHR to achieve near-zero suppression of low-frequency aerodynamic acoustic pressure. Furthermore, by adjusting the multiple parameters of LPNHR, the near-zero suppression of lower-frequency and larger-bandwidth aerodynamic acoustic pressure at higher speed could be achieved. Finally, an average reduction of sound pressure level by 3.71 dB (A) in the range of 550 Hz–4150 Hz on the 1/4-scale Ahmed body surface at a speed of 50 m/s is experimentally verified through 26 mm thick LPNHR metasurface with a basic unit composed of six parallel cells. The near-zero aerodynamic acoustic pressure suppression mechanism with metasurface presented provides new approaches for low frequency aerodynamic noise control, showing great potential in engineering applications.